2020
DOI: 10.3390/microorganisms8121989
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mediterranean Diet on Disease Activity and Gut Microbiota Composition of Rheumatoid Arthritis Patients

Abstract: Rheumatoid arthritis (RA) is an autoimmune disorder in which gut and oral microbiota play a crucial role. Diet is a modifiable factor that can influence both microbiota composition and arthritis outcome; previous studies have suggested associations between dietary habits and RA, with contrasting results. We investigate the protective effect of the Mediterranean diet (MD) on disease activity and the gut microbiota profile in RA patients. Sixty consecutive RA patients were enrolled upon filling a validated 14-it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 46 publications
3
33
0
2
Order By: Relevance
“…It is increased in CA and CRC patients [ 97 ] and decreased in obese individuals [ 98 ], which may explain the reduction observed in RS, which is a group defined by obesity and other commonly related clinical markers. According to the literature, Methanobrevibacter presented a low abundance in MD subjects [ 99 ]. The presence of Methanobrevibacter has been associated with the consumption of dietary fiber [ 100 ], but dairy products, which are consumed with moderation in MD, are also possible sources of M. smithii [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is increased in CA and CRC patients [ 97 ] and decreased in obese individuals [ 98 ], which may explain the reduction observed in RS, which is a group defined by obesity and other commonly related clinical markers. According to the literature, Methanobrevibacter presented a low abundance in MD subjects [ 99 ]. The presence of Methanobrevibacter has been associated with the consumption of dietary fiber [ 100 ], but dairy products, which are consumed with moderation in MD, are also possible sources of M. smithii [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Foods rich in fibers, such as those present in the Mediterranean diet (MD), indeed, are degraded by Firmicutes and Bacteroidetes into SCFA, such as butyrate [81,82], which can have a protective role on the gut barrier by reducing its permeability. We have recently found that RA patients with high adherence to MD have a lower disease activity joined to a healthier gut microbiota composition with a significant decrease in Lactobacillaceae and an almost complete absence of Prevotella copri in comparison with the low/moderate adherence patients [83].…”
Section: Vitamin D and Gut Microbiota Homeostasismentioning
confidence: 96%
“…Furthermore, gut microbiota composition changes with disease progression, and correlates with increased disease duration and seropositivity [58]. Adherence to a Mediterranean diet seems to restore this dysbiosis, leading to reduced CRP levels and lower disease activity in patients with established RA [59].…”
Section: Diet and Nutrition Prevention Researchmentioning
confidence: 99%